Sinar Surya Dari Balik Pare Muda: Peran KGPAA Mangkunegaran VII Dalam Pendidikan Keagamaan Islam di Mangkunegaran Tahun 1916-1944 - Musyafa', Mokhammad Fadhil (UIN Raden Mas Said Surakarta, 2021)
Mangkunegara VII was one of Boedi Oetomo’s actors which were elected to be Adipati ofMangkunegaran for giving the contribution through the roles during the throne. There are economic,social, cultural, and education. In the education case, Mangkunegara VII focused on Islamic religiouseducation.the researcher used the historical research method. there are Heuristic, Critics orVerification, Interpretation, and Historiography. The researcher found that Mangkunegara VIIestablishing trade schools for the economic sector, culturally revitalizing for the cultural sector, andseveral educational policies, especially in Islamic religious education. Keywords: Mangkunegaran,Mangkunegara VII, Islamic Religious Education.